Komponen-Komponen Pembelajaran dalam Kurikulum 2013 Pada Mata Pelajaran IPS - Adisel, Adisel; Aprilia, Zetira Utari; Putra, Ridwan; Prastiyo, Teguh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the learning components in the 2013 curriculum that have been applied in schools in social studies subjects. The method used in this study is a library study method, this method is carried out by collecting data from existing books and journals. The results of the study, one of the things that can be done to improve the quality of education is to improve the curriculum which focuses on the right method in the teaching process. The success of education cannot be separated from the role of education in managing and regulating the teaching and learning process, here it is not only focused on one-way information from the teacher but students must also be directly involved in various learning activities carried out. In conclusion, the implementation of learning is the result of the integration of several components that have their respective functions with the intention that the achievement of learning objectives can be met. In the learning strategy there are several components that must be considered by an educator, namely learning objectives, learning resources, learning strategies, learning media, and learning evaluation. Keywords: Learning components, Curriculum 2013, Social Sciences